Efeito da programação neurolinguística associada à terapia sonora no tratamento de pacientes com zumbido crônico : ensaio clínico randomizado controlado - Pereira, Laurinda Soares da Franca (2022)
Introduction: Tinnitus is a symptom that can negatively affect quality of life. Sound Therapy (ST) contributes to the reduction of discomfort through a sound generator, which accentuates the perception of environmental sounds and promotes the habituation of tinnitus in the Central Auditory System. Neurolinguistic Programming (NLP) is a tool that encourages assertive thinking and new choices. Objective: To evaluate the effectiveness of Neurolinguistic Programming associated with sound therapy in the treatment of tinnitus. Method: This is a randomized controlled, triple-blind clinical trial, carried out in individuals from a research group with chronic tinnitus, from a Higher Education Institution. They were randomly divided into two groups according to the intervention to be applied, sound therapy and Neurolinguistic Programming associated with sound therapy. The volunteers underwent otorhinolaryngological assessment, audiometric tests, Tinnitus Handicap Inventory questionnaire and Visual Analogue Scale. Interventions lasted thirty minutes with 5 sessions, performed 2,4,8 and 12 weeks after the first session. Sound therapy involved sound enrichment and counseling and, Neurolinguistic Programming, techniques for remodeling the mind map, anchoring and resignification. Results: The intragroup analysis showed that the group with NLP associated with sound therapy acted more expressively, reducing the perception, discomfort and severity of tinnitus (p<0.05). Conclusion: The use of NLP associated with sound therapy significantly improved cases of severe and catastrophic tinnitus more briefly than ST alone and contributed to the change from a marked degree of annoyance to a milder one.